Health economics theories, insights, and industry studies - Santerre, Rexford E.; Neun, Stephen P. (Sout-Western Cengage Learning, 2013)
Develop with a solid understanding of the costs and benefits associated with today's health care choices using the current, comprehensive coverage found only in HEALTH ECONOMICS: THEORY, INSIGHTS, AND INDUSTRY STUDIES, 6E, International Edition. Readers develop a practical, powerful knowledge of today's health care systems as the text builds upon only the core foundation of economic theory. This new edition reflects the latest updates and contemporary developments in insurance and health care reform, including a thorough update of the Nyman Theory and a new appendix covering the Grossman Model. Using a lively, inviting writing style, the book presents all topics in an easy-to-understand format with numerous real-world applications that readers can readily apply to their own lives.